(untitled) (Research, Society and Development, 2023)
This study reported a rare case of central precocious puberty in a male child, who was 2 years and 4 months old, with a history of gelastic seizures and signs of precocious puberty. The patient, at 1 year and 8 months old, exhibited pubic hair growth, increased penile and testicular size, and the onset of acne. Additionally, the child experienced unprovoked bouts of laughter (gelastic seizures) and daily behavioral changes, including aggression. An MRI examination of the pituitary gland revealed an expansive lesion in the hypothalamic region with partial obliteration of the posterior aspect of the suprasellar cistern and interpeduncular cistern, consistent with hypothalamic hamartoma. Treatment was initiated with GnRH analog and carbamazepine. The patient described here continues to receive pharmacological treatment.